96 Involving people with dementia who lack capacity in research. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Hopkinson, J; King, A; Hydon, K; Young, L; Howells, C; Tope, R; Muthukrishnan, S
Abstract : Background: Empowering people with dementia to be involved in research at all stages of the disease is, respectful of individuals, maintains personhood and is equitable. It is therefore consistent with best practice in dementia care. Research is important for improving dementia treatments, care and service delivery. However, involving people with dementia who lack capacity or who have fluctuating capacity in research is challenging and requires careful consideration to avoid potential harms. Methods: This paper reports a novel and successful method for recruitment into two research studies of people with dementia. The first study investigated cancer services provided for people with dementia who received cancer treatment in 2014/2015. The second study investigated crisis intervention in the community for people with dementia and their family members in 2017. The coproduced approach has enabled people with dementia in primary and secondary care receiving services in their own homes, out-patient clinics and in hospitals to take part in research. Results: This paper will discuss how the researchers: Devised method that accommodated the needs of people with dementia for obtaining formal written consent or support for participation from a Consultee, as required by the Mental Health Act 2005. Negotiated the challenges of ethical and other approvals. Developed training for research assistants in the assessment of mental capacity and recruitment of people with dementia. The presentation will include a flow diagram of the recruitment process. Other researchers should then be able to adopt or adapt the approach for studies involving people with dementia. Conclusions: There are challenges to involving people with dementia in research, but they can be overcome. What our research teams have learnt has informed the recently launched 'Research and impaired mental capacity in adults: guidance for researchers' published by Healthcare Research Wales. 1 Reference: . https://www.healthandcareresearch.gov.wales/uploads/News/research_and_impaired_mental_capacity_in_adults-guidance_for_researchers.pdf